Precocious puberty in a patient with Oculo-Auriculo-Verebral spectrum (OAVS) - A. Berio; G. Garlaschi; A. Piazzi (PAGEPress Publications, 2014)
The authors report on the first case of OAVS (Oculo-Auriculo- Vertebral-Spectrum), with hemifacial microsomy, hydrocephalus, pubertas precox, thelarche at 4 years of age, vaginal bleeding at 5 years, and left ovary of adult type on echography (right ovary initially not visualized). FISH and CGH-ARRAYS methods were negative. By GnRH therapy the delay of onset puberty was obtained. The authors ascribe facial and ovary asymmetry to a derangement of blastogenesis, during which axial right-left structures begin the develop with consequent migration or interation with surrounding tissues of neural crest cells and alteration of diencephalic pituitary systems.